Cover Image, Volume 9, Issue 8. Issue 8 (26th August 2019) - Ohoshi, Yuji; Takahashi, Shun; Yamada, Shinichi; Ishida, Takuya; Tsuda, Kumi; Tsuji, Tomikimi; Terada, Masaki; Shinosaki, Kazuhiro; Ukai, Satoshi
Abstract : The cover image is based on the Original Research Microstructural abnormalities in callosal fibers and their relationship with cognitive function in schizophrenia: A tract‐specific analysis study by Yuji Ohoshi et al., DOI:10.1002/brb3.1357 .